Sequências didáticas e ferramentas digitais: promovendo a aprendizagem significativa em estatística descritiva - Daroit, Luciane (2025)
Purely expository teaching and receptive learning have been increasingly questioned for not fostering the development of essential skills such as solving contextualized problem situations and critical thinking. Teacher-student interaction, combined with the adoption of new teaching strategies, is fundamental for the active and meaningful construction of knowledge. Teachers should create favorable conditions for students to autonomously develop knowledge, attitudes, and ways of thinking that contribute to their integral education. This research aimed to investigate the potential of a didactic sequence, combined with the use of digital technologies, in promoting evidence of meaningful learning. To this end, we developed two educational products: a didactic sequence structured according to the principles of Ausubel’s (2003) Theory of Meaningful Learning, and the TESTES chatbot – an artificial intelligence software – designed to answer students’ questions on Descriptive Statistics through explanatory texts and videos. The use of educational chatbots can promote active learning, as students are encouraged to explore, question, and apply statistical concepts in real situations. Chatbots can answer questions, provide additional explanations, and propose challenges for students to solve. The research problem addressed was: How can a didactic sequence structured on the basis of Ausubel’s Theory of Meaningful Learning, developed with the use of the TESTES chatbot as a support tool, contribute to meaningful learning in Descriptive Statistics? The general objective was to analyze how the proposed didactic sequence, using the TESTES chatbot, promotes meaningful learning in Descriptive Statistics. The study, conducted with 17 second-year high school students in the Basic Statistics course, focused on measures of central tendency and variability, and validated, over 12 sessions, the two educational products: the didactic sequence and the TESTES chatbot. The choice of this content is justified both by the difficulties observed in understanding basic statistical concepts and by their relevance in student education, reinforced by the BNCC, which highlights the need to develop such competencies. The analysis of the results showed that the proposed methodology, by integrating the didactic sequence with the use of the TESTES chatbot and explanatory videos, favored the consolidation and assimilation of concepts, promoting meaningful understanding, statistical literacy, and a more dynamic and contextualized teaching of Statistics. The organization of students into groups proved effective in knowledge exchange, fostering collaborative learning, the development of socio-emotional skills, and the collective construction of reasoning in a dynamic and participatory environment. Progressive student engagement was also observed, making the learning environment more dynamic and student-centered. Thus, this study highlights the importance of future research exploring computational applications and educational technologies in the teaching of Statistics, capable of enhancing concept understanding, personalizing teaching, stimulating collaborative work, and promoting motivation, autonomy, and meaningful learning – with emphasis on chatbots as an open field to make the teaching of Basic Statistics more effective, engaging, and aligned with students’ needs. This thesis is accompanied by the educational product, available on the EduCapes Platform at http://educapes.capes.gov.br/handle/capes/1174284.